FROM MINIMAL INTERFERENCE TO COMPREHENSIVE SAFEGUARDS: THE WRITTEN UNDERTAKING AND JUDICIAL OVERSIGHT - Stancheva, Kalina (E-Journal VFU, 2025)
The present report examines the legal nature, function, and challenges associated with the "written undertaking" measure under the Bulgarian Criminal Procedure Code. Although recognized as the least restrictive preventive measure, the lack of effective judicial review during the pre-trial phase raises significant concerns regarding the protection of the accused’s rights. This study highlights that written undertaking, despite its minimal 216 coercive impact, is not a mere administrative formality but a substantive procedural guarantee ensuring the accused’s participation in the criminal process. The absence of mandatory judicial oversight leads to unequal treatment compared to individuals subjected to more restrictive measures, as well as to procedural inefficiencies that compromise the principles of legality, necessity, and proportionality enshrined in Article 5 of the European Convention on Human Rights (ECHR). The report further explores the latent judicial control exercised through subsequent evaluation of evidence or future complaints, arguing that such mechanisms are insufficient to guarantee effective protection. In response, a legislative amendment is proposed to introduce explicit judicial review for personal recognizance, thereby aligning it with other preventive measures and strengthening procedural safeguards. The discussion also emphasizes the socio-economic advantages of this measure, as it allows the accused to maintain employment and social stability while incurring minimal public expenditure. Ultimately, the paper advocates for the integration of judicial oversight as a necessary step to ensure proportionality, fairness, and compliance with international human rights standards, reinforcing personal recognizance as both a humane and legally robust tool within the pre-trial process